1979
DOI: 10.2307/3800348
|View full text |Cite
|
Sign up to set email alerts
|

Methylmercury: Reproductive and Behavioral Effects on Three Generations of Mallard Ducks

Abstract: Three generations of mallard ducks (Ana~ platyrh!lncllo. s! "-'ere fed either a control diet or a diet containing 0.5 ppm mercury in the form of methylmercury. The !~vel$ of men.-ury in adult tissues and eggs remained about the same over 3 generations. The methylmercury di~ had no effect on adult weights or weight changes during the reproductive season. Females fed a diet containin~ 0.5 ppm mercury laid a greater percentage of their eggs outside their nestboxes than did controls, and also laid fewer eggs and p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
262
6

Year Published

1995
1995
2019
2019

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 325 publications
(272 citation statements)
references
References 15 publications
4
262
6
Order By: Relevance
“…The concentration of Hg in birds (as indicated by feather Hg) that causes deleterious effects, however, is subjected to numerous factors identified in the literature, including dietary composition, moult duration, phylogeny and ability to demethylate Hg in the liver [62][63][64]. In a review, Burger & Gochfeld [65] suggested that feather Hg between 5 and 40 mg g 21 dry weight rspb.royalsocietypublishing.org Proc.…”
Section: Discussionmentioning
confidence: 99%
“…The concentration of Hg in birds (as indicated by feather Hg) that causes deleterious effects, however, is subjected to numerous factors identified in the literature, including dietary composition, moult duration, phylogeny and ability to demethylate Hg in the liver [62][63][64]. In a review, Burger & Gochfeld [65] suggested that feather Hg between 5 and 40 mg g 21 dry weight rspb.royalsocietypublishing.org Proc.…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, the use of the most conservative TRVs may overestimate the actual risk of some contaminants to wildlife. For example, we initially used a TRV for mercury in bald eagle (0.0064 mg/kg/d) derived from a multi-generational study of mallards (Anas platyrychos ;Heinz 1979;Sample et al 1996). Based on this TRV, Yeardley et al (1998) estimated that mercury concentrations in fish from 98% of the lakes in the northeastern United States represented a risk to piscivorous birds.…”
Section: Dieldrin -Mink Dieldrin -Bald Eaglementioning
confidence: 99%
“…Thus, doses of 2 and 4 m g MeHg/g (dwt) were considered to be the dietary-based NOAEL and LOAEL values, respectively. However, both doses were greater than the LOAEL of 0.5 m g MeHg/g (dwt) (Heinz 1979 ) , which was determined from the results of a multigeneration exposure. The corresponding daily doses, which were converted from the dietary values using a rate of ingestion of food of 0.057 kg/kg (bm)/day, were 0.114 and 0.228 m g MeHg/g (bm)/day, respectively.…”
Section: Review Of Mehg Toxicity To Birdsmentioning
confidence: 99%
“…Based on multigenerational effects on reproduction, when converted from the dietary values by the use of rates of consumption of food of 0.156 kg food (wwt)/kg (bm)/day (US EPA 1995b ) , the dietary LOAEL value was 0.078 m g MeHg/g (bm)/day. Heinz ( 1974Heinz ( , 1975Heinz ( , 1976aHeinz ( , b, 1979 The corresponding concentrations of MeHg in tissues such as liver, kidney, breast muscle, brain, ovary, and primary feathers, and in eggs are given (geometric mean for three generations) for mallards (Heinz 1979 ; Table 2 ). Reproductive effects of MeHg on mallards were investigated by exposing adults to one of four doses of MeHg (1, 2, 4, or 8 m g MeHg/g (dwt)) (Heinz et al 2010a ) .…”
Section: Review Of Mehg Toxicity To Birdsmentioning
confidence: 99%